# Yahoo Web Search

related to K.C

1. Sort by

1. ### Probability math question?

Use the binomial probability formula: P(X = k) = C(n,k) * p^k * q^(n-k) n : number of trials (5) k : number...

2 Answers · Science & Mathematics · 12/01/2017

2. ### Linear Algebra eigenvalue proof question?

Write f(t) = ∑(i = 0, k) c_i t^i Since Av = λv, A^i(v) = A^(i-1)(Av...

1 Answers · Science & Mathematics · 27/11/2013

3. ### prove nCk = n-2Ck + 2(n-2Ck-1) + n-2Ck-2 Please explain and show all steps. Thanks!?

...be considered a double application of Pascal's rule: C(n,k) = C(n-1,k-1) + C(n-1,k) = C(n-2,k-2) + C(n-2,k-1) + C...

2 Answers · Science & Mathematics · 28/03/2016

4. ### determine the period ,amplitude and phase shift of f(x)=3cos2(x-pi/4)+1?

y= A cos (θ -d ) K + c A= amplitude , d horizontal shift, c= vertical shift, k = frequency per 2π or 360...

1 Answers · Science & Mathematics · 20/03/2011

5. ### 8 Choices, 4 spots = number of options?

Let C(n,k) be the binomial coefficient n!/k!(n-k)! (C(n,k) is the number of ways to select k things from...

1 Answers · Science & Mathematics · 30/07/2009

6. ### Math question!!!!!!!!!!!!!!!?

... Chris = C So basically: J + K = 19 K + C = 14 J + C = K 1) Use substitution postulate: it means...

1 Answers · Science & Mathematics · 09/02/2009

7. ### Data Management: Binomial Distributions?

...*. The binomial probability formula is: P(X = k) = C(n,k) * p^k * q^(n-k) n : number of trials (10) k : number...

3 Answers · Science & Mathematics · 09/01/2019

8. ### Rationals and Radicals. 1) Solve for k:E=1-c/k 2)Simplify.(Rationalize the denominator if necessary) a.sqrt5/3x^2 b.4sqrtb/sqrt3-b?

...that’s what you mean Multiplying both sides by k: Ek = kc Subtract k from both sides: Ek – k = -c Factoring...

2 Answers · Science & Mathematics · 16/01/2015

9. ### Math probability question?

Use the binomial probability formula. P(X = k) = C(n,k) * p^k * q^(n-k) n : number of trials (10) k : number...

3 Answers · Science & Mathematics · 31/12/2016

10. ### find y as a function of x if y'''+36y'=0 y(0)=-6 , y'(0)=-18, y''(0)=-36?

...solution is y(x) = c*e^(6i*x) + k*e^(-6i*x) + C. Now y(0) = c + k + C = -6. Next, y'(x) = 6i*c*e^(6i*x) - 6i*k*e^(-6i*x), so y'(0) = 6i...

1 Answers · Science & Mathematics · 24/02/2013